2006
DOI: 10.4049/jimmunol.176.11.6464
|View full text |Cite
|
Sign up to set email alerts
|

Selective Export of HLA-F by Its Cytoplasmic Tail

Abstract: MHC class I molecules exit the endoplasmic reticulum (ER) by an unknown mechanism. Although a selective export mechanism has been proposed for the anterograde transport of class I, a motif responsible for export has never been identified. Although classical class I molecules lacking their cytoplasmic tail are expressed on the cell surface, we found that HLA-F was entirely dependent on its cytoplasmic tail for export from the ER. Two known export motifs were recognizable in HLA-F. A C-terminal valine residue fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 52 publications
2
90
0
Order By: Relevance
“…Post-PLC, MHC I molecules are exported from the ER via a selective process, involving trafficking motifs in the HC cytoplasmic tails and Bap31, which facilitates recruitment into COP-II coated vesicles (31)(32)(33)(34)(35)(36). A bottleneck in the MHC I pathway appears to occur before the medial Golgi with the transport of suboptimally loaded MHC I molecules and PLC components blocked at this step (4,(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Post-PLC, MHC I molecules are exported from the ER via a selective process, involving trafficking motifs in the HC cytoplasmic tails and Bap31, which facilitates recruitment into COP-II coated vesicles (31)(32)(33)(34)(35)(36). A bottleneck in the MHC I pathway appears to occur before the medial Golgi with the transport of suboptimally loaded MHC I molecules and PLC components blocked at this step (4,(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, C⌬12 and C⌬15 share the presence of a COOH-terminal valine. This configuration promotes ER export for several full and truncated membrane proteins (14,16,38,39). However, unlike C⌬12, C⌬15 was not able to convert to mature form, strongly suggesting that the COOH-terminal valine is very unlikely to be the sole discriminating factor for C⌬12 export from the ER.…”
Section: Influence Of Cooh-terminal Truncations On the Steady Statementioning
confidence: 99%
“…To this regard, we recently demonstrated for the first time that WJ-MSC do express also other class Ib MHC molecules, namely HLA-E and HLA-F [45]: both are implicated in tolerogenic processes occurring at the foetomaternal interface, together with HLA-G [79][80][81]. Recent studies suggested additional functions for HLA-F other than antigen peptide loading [82,83]. Both HLA-E and HLA-F share a low genetic polymorphism (i.e.…”
Section: Recent Data On the Expression Of Relevant Immunomodulatory Mmentioning
confidence: 99%